Pathology of Bacillus piliformis infection in rabbits - Pawaiya, R V S; Mishra, N; Bhagwan, P S K (The Indian Journal of Animal Sciences, 2012)
Rabbits (92) died between April 1997 and March 1998 in the institute's rabbitry. On necropsy, 15 of these, belonging to all age groups, exhibited gross lesions of necrotic hepatitis with pin-point necrotic foci scattering uniformly in the liver parenchyma, haemorrhage typhlitis with serosal reddening involving adjoining parts of ileum and colon, and necrotic lesions in the heart. On histopathological examination, liver revealed small coagulative necrotic foci with leucocytic inflammatory cell reaction which demarcated from the surrounding viable hepatocytes. Caecal mucosa showed extensive necrosis and massive extravasation of erythrocytes; the lymphocytic and plasma cell reaction was also noticed predominantly. Caecal glands were hypertrophied and filled with mucinous substance. Heart revealed necrotic streaks in the cardiac musculature. On Warthin- Starry staining, viable hepatocytes around necrosis evinced intracellular clumps of long filamentous Bacillus piliformis organisms as also in the caecal mucosal epithelial cells and cardiac myocytes. This is probably the first detailed pathological study of Tyzzer's disease in Indian subcontinent.